Hubungan Posisi Kerja Dengan Keluhan Musculoskletal Disorder (MSDs) Pada Pemanen Sawit di PTPN IV Tanah Itam Ulu - Ananda, Zahra; Astuty, Delfriana Ayu; Indriani, Fatma (Fakultas Kedokteran Universitas Trisakti, 2025)
Background Musculoskeletal disorders (MSDs) are a common occupational health issue among plantation workers due to unergonomic working postures. Oil palm harvesters are especially vulnerable because of repetitive physical activities and awkward body positions. Work processes involving strenuous physical effort, such as lifting tools, cutting bunches, bending, and reaching for fronds for extended periods, along with unergonomic postures, increase the risk of MSDs. This study aims to determine the relationship between work posture and MSDs complaints among oil palm harvesting workers at PTPN IV Tanah Itam Ulu. Methods A cross-sectional quantitative study was performed with a sample of 50 Fresh Fruit Bunch (FFB) harvesters. Data were collected through observations and interviews using the Rapid Entire Body Assessment (REBA) to evaluate work posture and the Nordic Body Map (NBM) to assess MSDs symptoms. Data analysis was conducted using the Chi-Square test with a significance level of α = 0.05 in SPSS. Results The study revealed that 52% of workers experienced high-risk MSDs, while 48% faced very high-risk MSDs. A statistically significant relationship was identified between work posture and MSDs complaints (p = 0.000). Conclusions Poor ergonomic posture significantly increases the risk of MSDs among palm oil harvesters. Ergonomic interventions, including training on proper posture and the use of assistive tools, are strongly recommended to reduce risk and improve occupational health well-being.